Investigating 11 Withanosides and Withanolides by UHPLC–PDA and Mass Fragmentation Studies from Ashwagandha (Withania somnifera) - Girme, Aboli (ACS Omega, 2020)
[Image: see text] Withania somnifera (WS), also known as ashwagandha or Indian ginseng, is known for its pharmacological significance in neurodegenerative diseases, stress, cancer, immunomodulatory, and antiviral activity. In this study, the WS extract (WSE) from the root was subjected to ultrahigh-performance liquid chromatography with photodiode array detection (UHPLC–PDA) analysis to separate 11 withanoside and withanolide compounds. The quantification validation was carried out as per ICHQ2R1 guidelines in a single methodology. The calibration curves were linear (r(2) > 0.99) for all 11 compounds within the tested concentration ranges. The limits of detection and quantification were in the range of 0.213–0.362 and 0.646–1.098 μg/mL, respectively. The results were precise (relative standard deviation, <5.0%) and accurate (relative error, 0.01–0.76). All compounds showed good recoveries of 84.77–100.11%. For the first time, withanoside VII, 27-hydroxywithanone, dihydrowithaferin A, and viscosalactone B were quantified and validated along with bioactive compounds withanoside IV, withanoside V, withaferin A, 12-deoxywithastramonolide, withanolide A, withanone, and withanolide B simultaneously in WS. This UHPLC–PDA method has practical adaptability for ashwagandha raw material, extract, and product manufacturers, along with basic and applied science researchers. The method has been developed on UHPLC for routine analysis. The 11 withanosides and withanolides were confirmed using the fragmentation pattern obtained by the combined use of electrospray ionization and collision-induced dissociation in triple-quadrupole tandem mass spectrometry (TQ–MS/MS) in the WSE.